Pressing the Indian Growth Accelerator : Policy Imperatives - Mohan, Rakesh; Kapur, Muneesh (Washington, D.C. : International Monetary Fund, 2015)
India's real GDP growth slipped substantially after the North Atlantic financial crisis. Return to a sustained high growth trajectory is feasible but it will need much more focused attention to the revival of manufacturing and to the acceleration of investment in transport and infrastructure. The immediate priority is to achieve the kind of fiscal quality and low inflation levels exhibited during 2003-08, with focused attention to increasing efficiency and compliance in tax revenue collection. Higher tax revenues can facilitate increases in public investment, which then crowd in private investment. The task ahead will be more difficult in view of the protracted slowdown in global growth and trade.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet